Training on Creating Locally Context-Based Print and Digital Media for Tuberculosis Education for the Community - Shila Wisnasari; Elvira Sari Dewi; Fransiska Endang Widyastuti Dapi; Akhiyan Hadi Susanto; Yulian Wiji Utami; Titin Andri Wihastuti; Nurul Uswatin (International Journal of Community Service Learning, 2026)
The high number of Tuberculosis (TB) cases in Manggarai Regency, East Nusa Tenggara, indicates the low effectiveness of community health education. Furthermore, low public health literacy and communication practices lacking socio-cultural relevance, particularly in remote areas with complex cultural diversity, are contributing to the high number of TB cases. One cause is the lack of local context-based media in the delivery of information. This Community Service aims to analyze the effectiveness of training in creating locally context-based printed and digital educational media to improve the knowledge and skills of TB program managers. The type of activity used was participatory training with an andragogical approach, involving 25 TB program managers in Manggarai Regency. Data were collected through a pretest and posttest using a knowledge questionnaire and a skills observation sheet and analyzed descriptively. The results showed an 85% increase in participants' knowledge and a 72% increase in their ability to use simple applications to create educational media. This activity proved effective in increasing the capacity of TB program managers in developing locally context-based educational media. The implication is that similar training can be replicated in other regions to strengthen local culture-based health communication strategies.